Equine blastocyst re-expansion rate, quality, and sex following embryonic collapse using needle perforation of blastocoel and subsequent PCR amplification of blastocoel DNA - Camargo, Giovana S [UNESP]; Meira, Cezinande [UNESP]; Bergfelt, Don R; Oliveira-Filho, José P. [UNESP]; Bromberger, Cristiana R. [UNESP]; Barros, Luiz D. [UNESP]; Canesin, Heloisa S [UNESP]; Lopes, Giulia VR [UNESP]; Monteiro, Gabriel A; Ignácio, Fernanda S [UNESP] (Elsevier, 2023)
Collapse of equine blastocysts following needle perforation of the blastocoel prior to vitrification (Ferris et al., Journal of Equine Veterinary Science. 2016; 100:64-65) and collection and amplification of the free DNA blastocoel fluid may be used for sexing embryos (Herrera et al., Theriogenology. 2015; 83:415-420). The present study aimed to evaluate equine blastocyst re-expansion rate, quality, and sex following manual perforation of the blastocoel and PCR amplification of blastocoel fluid DNA. Embryos (n=19) were collected on day 8 after ovulation, assessed initially and transferred to a 50µL droplet of holding medium in which the blastocoel was manually perforated with a 26g hypodermic needle. Within one minute of detecting a diameter decrease or collapse, the entire volume of each droplet of medium was collected and stored at -20°C until PCR. Some of the collapsed embryos (n=11) were moved and immersed in 2mL of holding medium and cultured in isothermal boxes at 25°C. After 24h, embryo size and quality were reassessed. Post-culture, collapsed blastocysts had partially re-expanded to their initial diameter with a mean expansion rate of 68.8%. Quality of re-expanded embryos was Grade 2 (good, 6/11), Grade 3 (poor, 4/11), and Grade 4 (degenerated, 1/11) (McKinnon,Squires, J. Am. Vet Med. Assoc. 1988; 192:401-406). Non-perforated embryos (n=10) used as controls were initially Grade 1 (excellent, 8/10) and Grade 2 (2/10) and, after 24h of culture, Grade 1 (9/10) and Grade 2 (1/10) with a 25.9% growth rate. Blastocoel fluid from all collapsed embryos (n=19) was subjected to double PCR amplification of the male TSPY gene with blood of an adult male and female horse used as controls. Gene amplification indicated 57.9% (11/19) of embryos were male and non-amplification indicated 31.6% (6/19) of embryos were female. Gene amplification was inconclusive for 10.5% (2/19) of the embryos even though they were completely collapsed. Thus, needle-induced leakage and collapse of the blastocoel resulted in a high rate of blastocysts re-expansion (69%) with many embryos (54%) achieving good quality and potential for transfer as either male or female embryos. In , while the number of potentially transferable embryos that recovered from collapse was less than in the control group, the success of these preliminary results warrants further development to decrease damage and increase the culture re-expansion rate and quality of transferable male or female embryos for field application in an equine embryo transfer program.